Collaborative Border Management for Basic Infrastructure Development in Local Government Border Areas - Afni Noorani; Afif Syarifudin Yahya; Halilul Khairi; Hadi Prabowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
A country’s territorial integrity is crucial for maintaining sovereignty and must be protected through defense, security, and national unity. Indonesia’s independence was achieved through great sacrifices, making it essential to address threats such as inequality, injustice, and weakening national values. This research aims to analyze collaborative border management to accelerate the development of basic infrastructure in the North Borneo border area with Malaysia. This research employs a qualitative research design with a post-positivism approach to explore social phenomena in depth, develop theoretical interpretations, and answer the research questions. Collaborative border management has accelerated basic infrastructure development in Indonesia-Malaysia border areas, particularly in Nort Borneo. The government and private sector work together to improve road networks, inter-island transportation, water reservoirs, and telecommunications access. Providing subsidies to private entities can ensure affordable transportation services for residents while encouraging infrastructure expansion. Cross-border collaboration is essential for efficient development, enhancing accessibility, and improving the quality of life for border communities.